A Viking's love: and other tales of the North - Liljencrantz, Ottilie A. (Ottilia Adelina), 1876-1910; Becher, Arthur E., 1877-1960 (Salt Lake City, UT : Project Gutenberg, 2023)
"A Viking's Love: and Other Tales of the North" by Ottilie A. Liljencrantz is a collection of tales rooted in Norse mythology and Viking culture, written during the early 20th century. This book showcases a series of narratives that revolve around themes of honor, love, and the fierce warrior spirit of the Viking era, each story steeped in the rich traditions of the North. Through her careful research and storytelling, Liljencrantz captures the essence of Viking life, from battles and heroics to romantic entanglements. The first tale, "A Viking's Love," follows Sigurd Asbiornsson, who faces dire consequences after killing Thorer Sel, a boastful bailiff who has insulted him. As Sigurd awaits his fate, he seeks to convey a message to his love, Astrid, adding complexity to his situation. The subsequent stories in the collection explore similar themes, featuring characters who navigate their destinies through acts of bravery, loyalty, and often tragic love. Liljencrantz's tales depict both the grandeur and the harsh realities of life in the North, interweaving mythology and history to illustrate the timeless struggles between love and duty, courage and consequence, making this book a captivating read for enthusiasts of historical and mythological fiction. (This is an automatically generated summary.)
A Viking's love -- The hostage -- As the Norns weave -- How Thor recovered his hammer.
Release date is 2023-01-30
Richard Tonsing and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Vikings -- Fiction; Short stories, American